Property Restitution and the Return of Serb Refugees to Croatia - Mesić, Milan, sociolog (2011)
In this public lecture, the autghor reports on one of the key aspects of the representative national field resarch on return of Serb returnees to Croatia - property restitution to returnees - which he and D. Bagic carried out during autumn 2010. The quuestion is how much property restitution affected the real minority return.